The impact of being newly diagnosed with a bipolar disorder and the short‐term outcome of disorder‐specific management. (27th November 2013) - Parker, Gordon B; Graham, Rebecca K; Fletcher, Kathryn; Futeran, Shulamit M; Friend, Paul
<x xml:space="preserve">Abstract</x> Objectives The aim of the study was to determine the impact of a first‐time diagnosis of bipolar disorder in patients previously generally managed as having a unipolar disorder, and to quantify the impact of disorder‐specific management strategies for such newly diagnosed patients over the following three months. Methods A total of 157 patients receiving a diagnosis of bipolar disorder for the first time by a psychiatrist at a specialist depression clinic completed a research interview and questionnaires, with 106 (68%) also completing 12‐week quantitative and qualitative evaluations. Assessing psychiatrists undertook baseline and follow‐up assessments recording management changes, reactions to the diagnosis and global changes in functioning over time. Results The majority of patients had a positive response to receiving a diagnosis of bipolar disorder, and most implemented a number of clinician‐suggested bipolar management strategies. Patients showed improvement on five of the six self‐report measures over the three‐month study period. Multivariate analyses quantified lamotrigine as making the most distinctive contribution to 'improver' status, particularly for the bipolar II disorder subset. Conclusions Results are encouraging in identifying a generally positive acceptance of a diagnosis of bipolar disorder, improved outcome following the introduction of diagnostic‐specific management components, and a distinctive contribution of lamotrigine to improved three‐month outcome.